Stability of calcium in calcium-fortified pandesal - Adaoag, Cherry Joy Miguel; Dumelod, Benelyn Domingo (2000.)
ABSTRACT To help increase the calcium intake of Filipinos, this study on the calcium-fortification of pandesal, a popular breakfast item, was conducted. The commercial formulation of Meridian Bakery was fortified with calcium to meet 33% of the RDA for calcium for Filipinos 10 to 19 years old. Students t- test at α=0.05 revealed that there was no significant differences between the sensory attributes of the calcium-fortified and the unfortified(contol) samples. Replicability of the calcium-fortified pandesal was tested by producing three batches at 5-kg flour/batch. ANOVA at α- 0.05 indicated that the samples did not vary significantly due to production run. Thus production of calcium-fortified pandesal is replicable if the formulation and the process are strictly followed. Physico-chemical characterization of the calcium-fortified and control pandesal samples showed that the former contains 19.07% moisture, 6.65% crude fat, 9.90% crude protein, 58.63% available carbohydrates, 0.15% crude fiber and 5.60% ash. The latter contains 18.03% moisture, 479% crude fat, 9.2% crude protein, 64.58% available carbohydrates, 0.20% crude fiber and 2.49% ash. There was a considerable increase in the ash content of the calcium-fortified pandesal due to the addition of the calcium salt. The calcium content of a 40-g serving portion of calcium-fortified pandesal meets 31.08% of the RDA for the reference gorup while the control meets only 1.43%.The discrepancy between the calcium-content as analyzed and the amount added may be expained by losses during preparation. One piece of high-calcium pandesal costs P0.86, ie P0.07 more than the cost of the unfortified pandesal.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Bread; Enriched food